2018
DOI: 10.31018/jans.v10i1.1622
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Trichoderma against Sclerotium rolfsii causing collar rot disease of lentil under in vitro conditions

Abstract: Three biocontrol agents viz., Trichoderma viride, T. virens and T. harzianum were evaluated to test the antagonism against Sclerotium rolfsii under in vitro conditions. All the three antagonists' viz., T. viride, T. virens and T. harzianum have shown the potential of parasitizing the growth of Sclerotium rolfsii in vitro. The rate of inhibition was fastest in T. harzianum (63.60%) followed by T virens (51.5 %). Least inhibition was recorded in T. viride (50.85% ) after 72 hours of incubation. However, T. virid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 11 publications
1
3
0
Order By: Relevance
“…2 ), this study also confirmed that MetA1 produces antifungal metabolites. This was in line with previous reports, which found that CFCs produced by hypocrealean fungi were effective at inhibiting the growth of fungal pathogens [ 21 , 23 , 49 , 50 ]. A recent study found that CFCs of M. anisopliae containing active toxic compounds and secondary metabolites damaged the mycelium and conidial plasma membrane integrity of the mold-causing fungus Botrytis cinerea, respectively [ 21 ].…”
Section: Discussionsupporting
confidence: 93%
“…2 ), this study also confirmed that MetA1 produces antifungal metabolites. This was in line with previous reports, which found that CFCs produced by hypocrealean fungi were effective at inhibiting the growth of fungal pathogens [ 21 , 23 , 49 , 50 ]. A recent study found that CFCs of M. anisopliae containing active toxic compounds and secondary metabolites damaged the mycelium and conidial plasma membrane integrity of the mold-causing fungus Botrytis cinerea, respectively [ 21 ].…”
Section: Discussionsupporting
confidence: 93%
“…Similar results were also observed in studies by [21] where they evaluated "effects of different culture media on S. rolfsii mycelial growth, sclerotial production". [22] examined "total of seven media were used for studying the growth of S. rolfsii in Lentil" and [23,24] also proved "the efficiency of PDA in enhancing mycelial growth of fungus out of nine different cultural media. Their results reported that potato-dextrose medium was most suitable for mycelial growth and sclerotia production of S. rolfsii.…”
Section: Discussionmentioning
confidence: 99%
“…The principal biocontrol mechanisms involved include mycoparasitism, antibiosis, competition, and induced resistance ( Kumar et al 2009, Kumar. 2013, Chaudhary et al, 2017, Kushwaha et al, 2018. Application of bioagents in a consortium may improve the efficacy, reliability and consistency of the bioagents even under diverse soil and environmental conditions (Sharma et al 2012…”
Section: Evaluation Of Antagonistic Efficacy Of Volatile and Non Volatile Compounds From Consortium Of Trichoderma Against Fusarium Udummentioning
confidence: 99%